The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1055/s-0034-1372508
|View full text |Cite
|
Sign up to set email alerts
|

Dichotic Hearing in Elderly Hearing Aid Users Who Choose to Use a Single-Ear Device

Abstract: Introduction Elderly individuals with bilateral hearing loss often do not use hearing aids in both ears. Because of this, dichotic tests to assess hearing in this group may help identify peculiar degenerative processes of aging and hearing aid selection. Objective To evaluate dichotic hearing for a group of elderly hearing aid users who did not adapt to using binaural devices and to verify the correlation between ear dominance and the side chosen to use the device. Methods A cross-sectional descriptive study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Because of the complaints and audiological results, all the subjects have been wearing a hearing aid for more than six months. The use of hearing aids has been reported as having a major role in the treatment of tinnitus 10,11,16 , but in this sample there was no remission of symptoms.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Because of the complaints and audiological results, all the subjects have been wearing a hearing aid for more than six months. The use of hearing aids has been reported as having a major role in the treatment of tinnitus 10,11,16 , but in this sample there was no remission of symptoms.…”
Section: Discussionmentioning
confidence: 61%
“…The use of hearing aids, in addition to minimizing the effects of hearing loss, contributes to decreased tinnitus perception 5,10,11 . However, there are patients that continue to complain about the presence of symptoms even after adapting to their hearing aid.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have reported that elderly patients with bilateral hearing loss sometimes choose unilateral HAs because the use of 2 HAs causes greater disturbance. 7 Elderly patients can have central auditory processing disorders due to the aging process of the peripheral and central auditory pathways. This process could result in decreased auditory information processing, leading to difficulties in verbal and non-verbal information processing.…”
Section: Discussionmentioning
confidence: 99%
“… 6 This has been attributed to different causes: economic, aesthetical, and subjective discomfort related to the phenomenon of binaural interference. 7 …”
Section: Introductionmentioning
confidence: 99%
“…30 older users of hearing aids (60–81 years) who used only 1 hearing aid, mostly on the right side, could not fulfill the dichotic test items at 100%. 94% only used one hearing aid because 2 devices were perceived as too loud and disturbing, 6% had esthetical reasons [ 29 ]. However, hearing aids help affected people also to cope with tasks of their daily life which was shown by an investigation from Brazil showed in 17 first hearing aid users.…”
Section: Process Of Hearing Aid Provision: Specialist Versus Hearinmentioning
confidence: 99%